CIPP-BASED EVALUATION OF ONE-MONTH TAHFIDZ PROGRAM: INSIGHTS FROM YAYASAN KARANTINA TAHFIZ AL-QUR’AN IN WEST JAVA - Achmadi, Ali; Ernawati, Ernawati; Ghani, Abdul Rahman A.; Giyanti, Giyanti (World Psychology, 2025)
This research evaluates One-Month Tahfidz Program at Yayasan karantina Tahfidz Nasional (YKTN) in West Java using CIPP Model. Data were collected through observations, interviews, and document study. The findings show that the program vision dan mission are relevant to Muslim society needs, offering opportunities for participants from diverse background. Input such as facilities and qualified instructors are adequate, though pedagogical skills require improvement. The process evaluation highlights the effectiveness of Yadain method and intensive scheduling, yet some participants face fatigue and differing learning styles. Product evaluation indicates significant outcomes: 30% of participants completed 30 Juz, while most achieved 15–25 Juz with an error rate of 2–4% and retention of 96–98%. Overall, the program is effective, but requires follow-up mechanisms to maintain long-term memorization.